Fodder and labour for augmenting milk production in hills: A case study of Meghalaya - Sheikh, Feroze Mohammad; Singh, Ram; Sirohi, Smita (Indian Journal of Dairy Science, 2017)
The role of fodder and labour is recognized in increasing milk productivity but the evidences are lacking in the north eastern hills of India. Hence, the present paper is an attempt to estimate the effect of fodder and labour on milk productivity in Meghalaya.Â A randomly selected sample of 300 dairy farmers of Ri-Bhoi and East Khasi hill districts were interviewed during 2013-14. The study revealed that primarily family labour was utilised for maintaining cows. The local cows were fed on grazing and crossbred cows were stall fed. Hay was the only dry fodder; and grass and leaves were the green fodder fed to the dairy cows. The amount of feed and labour positively influence the milk productivity in the hills of Meghalaya. Scientific nutrition management and introduction of fodder crops may augment the milk productivity in the hills.